ANALISIS LITERATUR PENGGUNAAN MEDIA KARTU DALAM PEMBELAJARAN BAHASA INDONESIA SEKOLAH DASAR SERTA INOVASI KOMIK KARTU KATA DIGITAL - Mailatul Maftukhah; Mintarsih Arbarini; Haryadi; Bernadus Wahyudi Joko Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to systematically review several studies related to reading ability and vocabulary mastery in Indonesian language learning at elementary schools. Reading ability and vocabulary mastery are the main foundations of Indonesian language learning in elementary schools. The three previous studies show that card-based media, including word cards, flashcards, and picture word cards, have a positive effect on improving students' basic literacy skills. This article aims to review and compare previous research on the use of card media in learning Bahasa Indonesia at elementary schools and proposes the development of digital word card comics as an alternative medium that is more interactive and contextual. The research method used was a literature review of three empirical articles and other relevant supporting sources. The study results indicate that card media is effective in improving students' reading skills and vocabulary mastery, but it remains conventional. Therefore, digital word card comic media is proposed as an innovative form of 21st-century learning media that integrates text, images, and audio in a digital context.